Sustainability and corporate governance : a guide to law and practice - Gutterman, Alan S., 1955- (London : Routledge, 2020)
Sustainability and Corporate Governance is the first extensive and targeted guide for directors and their legal advisors on creating a governance framework for corporations that integrates all the recognized principles of sustainability now being discussed in boardrooms all over the world. The book provides a step-by-step approach on integrating sustainability principles into the activities of the board of directors including detailed guidance on legal, regulatory and business aspects of organizing and operating board committees and designing the sustainability management unit. Essential topics covered include: Elements of an effective framework for implementation of sustainability governance, including required policies, procedures and committee charters Organization of the governing board to effectively address sustainability issues and implement sustainability strategies Best practices and processes to engage company stakeholders Corporate board members and attorneys will appreciate the book's practical forms and checklists, complete coverage of all facets of sustainability governance, summaries of relevant international and national guidelines and instruments, and a curated list of samples and case studies from companies all around the world.
OCLC-licensed vendor bibliographic record.
Keywords: Corporate governance -- Law and legislation; Social responsibility of business -- Law and legislation; Sustainability; BUSINESS & ECONOMICS / Green Business; BUSINESS & ECONOMICS / Business Law